A Rapidly Deployable Test Suite for Respiratory Protective Devices in the COVID-19 Pandemic. (September 2020) - Blad, Thijs; Nijssen, Joep; Broeren, Freek; Boogaard, Bob; Lampaert, Stefan; van den Toorn, Stefan; van den Dobbelsteen, John
Introduction: The current COVID-19 pandemic has caused large shortages in personal protective equipment, leading to hospitals buying their supplies from alternative suppliers or even reusing single-use items. Equipment from these alternative sources first needs to be tested to ensure that they properly protect the clinicians that depend on them. This work demonstrates a test suite for protective face masks that can be realized rapidly and cost effectively, using mainly off-the-shelf as well as 3D printing components. Materials and Methods: The proposed test suite was designed and evaluated in order to assess its safety and proper functioning according to the criteria that are stated in the European standard norm EN149:2001+A1 7. These include a breathing resistance test, a CO2 build-up test, and a penetration test. Measurements were performed for a variety of commercially available protective face masks for validation. Results: The results obtained with the rapidly deployable test suite agree with conventional test methods, demonstrating that this setup can be used to assess the filtering properties of protective masks when conventional equipment is not available. Discussion: The presented test suite can serve as a starting point for the rapid deployment of more testing facilities for respiratory protective equipment. This could greatly increase the testing capacity and ultimately improve the safety of healthcare workers battling the COVID-19 pandemic.